Mechanical, thermal and optical properties of new chloroantimonite glasses in the Sb₂O₃–PbCl₂–AgCl system - Yezli, D.; Legouera, M.; El Abdi, R.; Poulain, M.; Burgaud, V. (Фізико-хімічна механіка матеріалів, 2016)
New chloroantimonite glasses were obtained in the Sb₂O₃–PbCl₂–AgCl ternary system. Thermal, optical and mechanical properties were studied. The silver chloride concentration was increased at the expense of antimony oxide according to the following composition rules: (80–x)Sb₂O₃–20PbCl₂–xAgCl; (70–x)Sb₂O₃–30PbCl₂–xAgCl. Depending on AgCl content, Vickers micro-hardness varied between 110 MPa and 140 MPa. Elastic moduli were measured by ultrasonic velocity. The optical transmission range extended from 400 nm in the visible spectrum to 7 mm in the infrared spectrum. The refractive index was close to 2. Glass transition temperature measured by DSC ranged from 250 to 290°C. It was noticed that the glass transition temperature decreased as AgCl substitute for Sb₂O₃ and the more stable system was with 20% PbCl₂ in the (80–x)Sb₂O₃–20PbCl₂–xAgCl.